An Understanding of Transporter Serotonin Genotype Profile and Mood Status among Nurses is Important Related to Work Productivity - -, Susy Purnawati (Prosiding Seminar Nasional Sains dan Teknologi (Senastek); Vol 8 No 1 (2023): Senastek 2023, 2023)
Abstract — The large quantitative and qualitative workload of nurses is a source of stressors that can pose a risk to their health and productivity. Variant genotypes of the serotonin transporter (5-HTTLPR) play a role in influencing an individual's capacity for stress response. Serotonin levels as a product of the mechanism of the serotonergic system (including the involvement of the serotonin transporter in its function of re-uptaking serotonin, the process of transporting the neurotransmitter serotonin from the synaptic cleft back to the presynaptic neuron) affect the mood status and work productivity. The study aimed to find out how the nurse's serotonin transporter genotype variant and mood status influence the risk of mental illness related to job stressors. M ethod : this study is a preliminary exploratory study to increase nurses' awareness and understanding regarding the risks of occupational mental illness. Results : The s/s type of serotonin transporter variant is characterized by the individual leading to less transcription for the SLC6A4 gene, and it has been found that it can partly account for anxiety-related personality traits. In addition, they tend to have low serotonin levels which are reflected by low mood status with the risk of impaired work productivity, especially with unergonomic night shift work arrangements. Apart from the role of genetics, the risk of mental health problems among nurses in the workplace is also influenced by working conditions, especially in high demands, low rewards, and low workplace social capital jobs where psychosocial job stressors increase among this type. This genotype has also been reported to have cortisol reactivity levels that can be enhanced or weakened when faced with environmental stress. C onclusion : information on the availability of data on serotonin transporter genotype variations is very important regarding worker placement and occupational mental health risk. Nurses with the s/s type have a higher risk of experiencing work-related anxiety or depression than the other two types.   Key word — genotype, health care worker, serotonin transporter